The complete gardener - Don, Monty (Dorling Kindersley Limited, 2021)
This extensively revised new edition of his Complete Gardener, first published in 2003, brings you right up-to-date on how Monty gardens today - and his recommendations for you. The most comprehensive, practical, and highly illustrated book Monty has ever written, it covers what he believes are the most important aspects of gardening. Organic techniques have always been at the core of his practice, but this new edition picks up on another key principle: the need to provide habitats in your garden for local wildlife.